Perinatal depression and suicidal behaviour: the need for timely intervention - Rathore, Ghanshyam; Sharma, Kanchan; Yadav, Nisha; Jha, Sujata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
This review examines perinatal depression, including antenatal (pregnancy-related) and postnatal (after childbirth) depression. It highlights their prevalence, risk factors, symptoms, and impacts on women and families, such as premature birth and significant maternal mental health issues. Causes include environmental stressors, genetic predisposition, and hormonal changes. The review distinguishes between temporary "baby blues" and prolonged postnatal depression influenced by social, psychological, and biological factors. Risk factors include negative family dynamics, a history of mental health issues, and lack of social support. Emphasizing the need for timely intervention and comprehensive mental health care, this review used a comprehensive search strategy across databases like PubMed, Google Scholar, Scopus, and more. Keywords related to perinatal depression were used for screening abstracts and titles, with full-text articles assessed for eligibility. Quality was evaluated using tools like the Newcastle-Ottawa scale (NOS) and the critical appraisal skills programme (CASP). Findings highlight the importance of regular mental health screenings, psychotherapeutic approaches, pharmacological treatments, and robust support systems. Understanding the interactions between biological, psychological, and social factors in perinatal depression is crucial for improving maternal and fetal health outcomes.